Avifauna and Grading Assessment of the Wetlands in South-West Coast, Korea - Yong-Un Shin; Tae-Han Kang; In-Kyu Kim; Si-Wan Lee; Hong-Shik Oh (한국조류학회지, 2014)
In this study a survey was conducted on birds, visiting the West-South Coast in Korea from July in 2007 to March in 2013, in order to look into the Avifauna and the grading assessment of the tidal flat at twelve wetlands in the West-South coast. The survey results revealed that there existed 191 species in total. The dominant species were Dunlin (Calidris alpina), Bean Goose (Anser albifrons), White-fronted Goose (Anser albifrons), Black-tailed Gull (Larus crassirostris) and Bar-tailed Godwit (Limosa lapponica); in the order of dominancy. In score grading, Seocheon tidal flat and Cheonsu bay were at the highest grade level. In addition, in ranking grade, Hauido Is., Doam bay and Muan bay were relatively higher than the others. The score grade and ranking of the Seocheon tidal flat was higher than other wetlands. The Seocheon tidal flat is an undeveloped natural tidal flat. An artificial environment of the Cheonsu bay was at the highest level in score grade, however it was at a low level in ranking grade. The tidal flat grading assessment used was able to efficiently evaluate the objective data in the management of the tidal flat. However, for accurate assessment in this study, the characteristics of each tidal flats had to be presented. KCI Citation Count: 1